Analysis of The Impact of Inflation, Interest Rates, and Exchange Rates on LQ45 Stock Prices on the Indonesia Stock Exchange (2020–2025 Period) - Myria Dwiastuti Wiranda; Riyandi Nur Sumawidjaja; Nunung Ayu Sofiati (Jurnal Investasi Islam, 2026)
Macroeconomic fluctuations are among the primary factors influencing stock price movements in the capital market. However, previous studies have reported inconsistent findings regarding the effects of inflation, interest rates, and exchange rates on LQ45 stock prices during the post-pandemic period, indicating the need for further empirical investigation. This study aims to examine the effects of inflation, interest rates, and exchange rates on the stock prices of companies listed in the LQ45 Index of the Indonesia Stock Exchange during 2020–2025. A quantitative approach was employed using secondary data obtained from the Indonesia Stock Exchange, Bank Indonesia, and Statistics Indonesia. The data were analyzed using multiple linear regression after satisfying the classical assumption tests. The results reveal that inflation has a significant negative effect on stock prices, while interest rates also exert a significant negative influence. Conversely, the exchange rate has a significant positive effect on stock prices. Simultaneously, these macroeconomic variables significantly affect stock prices, with an Adjusted R² of 66.6%, indicating that the proposed model explains a substantial proportion of stock price variation. These findings highlight the importance of macroeconomic stability in supporting capital market performance. The study provides practical implications for investors in developing investment strategies based on macroeconomic indicators and for policymakers in designing monetary and economic policies that promote market stability and strengthen investor confidence.